2022
DOI: 10.3390/ma15155273
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Numerical Modeling of the Impeller Construction Impact on the Aluminum Degassing Process

Abstract: This paper presents the results of tests on the suitability of designed heads (impellers) for aluminum refining. The research was carried out on a physical model of the URO-200, followed by numerical simulations in the FLOW 3D program. Four design variants of impellers were used in the study. The degree of dispersion of the gas phase in the model liquid was used as a criterion for evaluating the performance of each solution using different process parameters, i.e., gas flow rate and impeller speed. Afterward, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The shape of the bubbles before disintegration indicates that vortex structures in the vessel are largely involved in this process. The authors also confirmed that the gas flow has an impact on bubble size, which increases with increasing gas flow and decreasing rotor rotational speed [31,34,35]. Bubble dispersion as a function of rotor speed was explored in [36].…”
Section: Introductionmentioning
confidence: 69%
“…The shape of the bubbles before disintegration indicates that vortex structures in the vessel are largely involved in this process. The authors also confirmed that the gas flow has an impact on bubble size, which increases with increasing gas flow and decreasing rotor rotational speed [31,34,35]. Bubble dispersion as a function of rotor speed was explored in [36].…”
Section: Introductionmentioning
confidence: 69%
“…The refining ladle was replaced by a container of a similar volume but made of a material allowing for monitoring the phenomena inside the refining ladle. fields during the refining, but also the refining process itself [11][12][13][14][15][16][17][18][19]. The CFD m also one of the options to verify whether the wear process of the rotor has a neg positive impact on degassing efficiency, or to perform the optimization of the r peller shape itself.…”
Section: Basic Fdu Geometrymentioning
confidence: 99%
“…Proc. 2024, 60, 13 2 of 6 fields during the refining, but also the refining process itself [11][12][13][14][15][16][17][18][19]. The CFD method is also one of the options to verify whether the wear process of the rotor has a negative or a positive impact on degassing efficiency, or to perform the optimization of the rotary impeller shape itself.…”
Section: Geometry Of the Rotor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture surfaces of the post-mortem tensile bars showed both blowholes and oxide layers, responsible for lowering the strength properties of the tested alloy. In addition to the above-mentioned tests, aluminum casting alloys were the subject of many other tests in terms of their degassing and hydrogen content [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%